Analysis of risk factors for changes of left ventricular function indexes in Chinese patients with gout by echocardiography - Dang, Wantai; Luo, Danling; Hu, Jing; Luo, Hui; Xu, Xiaohui; Liu, Jian (Frontiers in Physiology, 2023)
Background: Echocardiographic data investigating the association between left ventricular (LV) function and gout is still limited.To analyze the association of echocardiographic parameters based on two-dimentional speckle tracking analysis with clinically related indicators in patients with gout, and to provide a clinical basis for the early diagnosis and treatment of cardiovascular disease in patients with gout.Methods: This study collected gout patients who visited the outpatient and inpatient departments of the first affiliated hospital of chengdu medical college from November 2019 to December 2020. Spearman correlation test was performed to analyze the correlation coefficients between the laboratorial indicators with echocardiographic parameters. And the logistic regression analysis was performed to evaluate the independent effects.The results of multivariate logistic regression showed that fasting plasma glucose (FPG) was a risk factor for the decrease in absolute value of global longitudinal strain (GLS [OR=2.34; 95% CI, 1.01-5.39; P=0.04]), Urea was a risk factor for absolute reduction in GCS (OR=1.40; 95% CI, 1.07-1.85; P=0.02), age (OR=1.09, 95% CI, 1.04-1.16; P=0.001), and hypertension (OR=8.35; 95% CI, 1.83-38.02; P=0.006) were risk factors for increased E/Em. High urea levels were significantly related with high risks of LVH (OR=1.59, 95% CI, 1.04-2.43; P=0.03) and enlargement of LAVI (OR=1.68, 95% CI, 1.01-2.80; P=0.04). This is a provisional file, not the final typeset article Conclusion: Our study found that elevated urea and FPG were risk factors for subclinical LV myocardial dysfunction in patients with gout, which might provide a theoretical basis for the early diagnosis and treatment of heart disease in clinical practice.